Acquisition of a foreign language by solving communication problems. - Arias, Rodrigo; Duque, Alvaro; Mitchell, Yanik (Íkala, Revista de Lenguaje y Cultura, 1997)
Teaching of foreign languages (FL) is a discipline that has resulted from a long historical development and has been nourished by diverse knowledge. Consequently, its practice leads to healthy discrepancies and a great variety of methodological proposals. However, there has often been a division between the theoretical-philosophical postulates of the different methodological approaches and their daily practice in the classroom. Some of the instructional approaches have claimed to have FL communication as the ultimate goal, nevertheless, innumerable didactic implications derived from the concept of communication have remained untransferred to the practice of the foreign language classroom. An insistence on the merely linguistic aspects, particularly in the four skills, has led to a neglect if not oblivion of the extra and paralinguistic symbols, which distorts the communication process. What often occurs then is a separation between the communication proclaimed in the methodology and in the syllabus, and the praxis that takes place in the classroom, since the foreign language as a system ( focusing on grammatical and phonetic rules, etc.) continues to be emphasized and not the performance in FL (with its semantic and pragmatic dimension). This mistaken comparison between linguistics and communication has led to an erroneous methodological praxis, with disastrous consequences for coherence and efficacy.